Simulation of Wind Speed Effect on the Fall Velocity of Raindrops - Sefri Ayuliana; Suhrawardi Ilyas; Fashbir . (Journal of Aceh Physics Society, 2013)
Raindrop motion is affected by several factors; one of which is wind speed during the rain. This study is aimed to investigate that impact by using mathematical simulation with Fortran and Matlab. Raindrops arrive on the Earth’s surface at their terminal velocities which depend on their size. Raindrop falling motion could be analyzed with net force equation (Newton’s second law). In order to determine velocity and position equations as a function of time, coefficients in those equations were fitted and compared toraindrop model developed by Boxel in 1997. In this study, equations used are fitted to both large and small size raindrops. Values resulted by equation for large size drops agreed with experimental data. Wind speedcauses the terminal velocities of raindrops to get larger, and so does their kinetic energy. In that condition, raindrops fall with certain inclination angle. The stronger wind speed, the larger raindrops’ inclination angle and their kinetic energy are when hitting soil surface. Therefore it increases the risk of soil erosion at place where the soil is unstable. Through this study, speed and direction of raindrop when hitting soil surface could be investigated in order to decrease the risk of avalanche at high risk area.